Recent advances on humic acid removal from wastewater using adsorption process - Tamara Alomar (17746770) (2023)
Humic acid (HA) is a component of natural organic matter (NOM) with a high molecular weight and high complexity. The presence of humic acid in water raises serious concerns due to its toxicity and ability to form carcinogenic trihalomethanes. Adsorption was shown to be an effective method for the removal of humic acid from various wastewater sources. Many adsorbents were feasible and effective for removing HA from wastewater, including carbon-based and activated carbons, clay-based adsorbents, zeolites, iron-based/magnetic adsorbents, functionalized adsorbents, and natural adsorbents. The removal of humic acid from water using different types of adsorbents was presented and reviewed and the effect of changing operational parameters such as pH, adsorbent dosage, contact time, initial HA concentration, temperature, and ionic strength on humic acid adsorption performance was evaluated. According to the review, the nano-MgO adsorbent performed the best in humic acid removal capacity, while MAER-3 resin performed the most regeneration cycles. Nano-MgO was the most promising adsorbent in capacity and regeneration capabilities, with an adsorption capacity of 1260 mg/g and ten regeneration cycles. Future research should focus on continuous adsorption processes in order to scale-up and use on an industrial level, as well as using actual wastewater rather than synthesized wastewater for adsorption experiments, as well as cost analysis to determine the feasibility of scaling up on an industrial level. Other Information Published in: Journal of Water Process Engineering License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jwpe.2023.103679